Effect of Transcranial Direct Current Stimulation on Endurance Performance in Elite Female Rowers: A Pilot, Single-Blinded Study - Zhiqiang Liang; Junhong Zhou; Fujia Jiao; Trenton Gin; Xi Wang; Yu Liu; Jiaojiao Lü (Brain Sciences, 2022)
Endurance, which is dependent at least partly upon the activation of the brain cortex, is important for performance in rowing. Transcranial direct current stimulation (tDCS) has shown benefits for endurance, but its effects on the endurance performance of elite rowing athletes are unknown, and are examined in this study. Eight elite female rowers completed 5 km of rowing on an ergometer following stimulation of the tDCS and sham over motor cortices. Each session lasted 20 min and the current was set at 2.2 mA. Time, 500 m/split, power, time corresponding to 500 m (TC500) and power corresponding to 500 m (PC500) were recorded continuously throughout the tests. No significant differences in time, 500 m/split and power were observed between baseline, tDCS and sham. Compared to the sham, tDCS induced a percentage reduction in TC500 from baseline to 2500 m and 4000 m, and a percentage increase in PC500 from baseline to 500 m, 1000 m, 1500 m, 2000 m, 2500 m, 4000 m, 4500 m and 5000 m. One-session tDCS did not have significant benefits for rowing endurance performance in elite professional rowers, and had only marginally greater efficacy compared to sham. These findings offer knowledge helpful to the design of future studies exploring the effects of tDCS on the endurance performance of elite rowers.